2015
DOI: 10.1016/j.pbb.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and carbon monoxide exposure from inhalation of cigarillo smoke

Abstract: Background There has been an increase in the use of cigarillos in the US. People who smoke cigarillos typically also regularly smoke cigarettes (dual users). Methods We compared puffing topography, biomarkers of acute exposure [exhaled carbon monoxide (COex) and plasma nicotine] and physiologic effects from usual brand cigarette and Black & Mild cigarillo smoking in dual users (N=23) in two laboratory sessions. Results Participants (21 men) smoked an average of 17.5 cigarettes/day. Cigarillo consumption va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 41 publications
4
54
0
Order By: Relevance
“…However, little cigars deliver much greater amounts of CO compared with cigarettes after adjusting for consumption. Enhanced CO generation from cigar smoke has been observed in studies from our laboratory and others,22 33 47 55 and is usually attributed to less complete combustion of the tobacco filler due to the larger diameter, more dense packing and less porous wrapping 55…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, little cigars deliver much greater amounts of CO compared with cigarettes after adjusting for consumption. Enhanced CO generation from cigar smoke has been observed in studies from our laboratory and others,22 33 47 55 and is usually attributed to less complete combustion of the tobacco filler due to the larger diameter, more dense packing and less porous wrapping 55…”
Section: Discussionmentioning
confidence: 83%
“…Procedures have been described previously 22. Briefly, participants completed a two-visit study in which they were randomised to smoke either a Winchester little cigar (85 mm, filtered, filter-ventilated) or their own brand of cigarette at each session.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have examined the abuse potential of cigars by assessing craving and withdrawal symptoms, and have demonstrated that cigar smoking effectively alleviates many of these symptoms. 812 …”
mentioning
confidence: 99%